Development of Computer-Assisted Language Learning Literacy Framework for Foreign Language Teachers - Tafazoli, Dara (Online Learning, 2025)
The increasing interest in integrating technology into language education compelled language teachers to upskill their competencies and literacies. Therefore, a need for a framework to meet teachers’ needs is a must. To meet the end, I conducted two studies in two different teaching contexts. The first is a phenomenological study interviewing 12 foreign language teachers in Iranian higher education to determine the main components of the computer-assisted language learning (CALL) literacy framework and its influential factors. The second study aims to validate the emerged framework from the first study through the Delphi method by ten Persian language experts. The findings showed that CALL literacy is the interplay between language literacy, teaching literacy, and digital literacy, and influential factors on teachers’ CALL literacy are academic degree and qualifications, cognitive abilities, communicative competence, intercultural competence, managerial competence, creativity, and being culturally responsive, which are all nested in the context. The findings of the study provide some implications for language teachers and teacher educators.